Professional Engineer's Roles and Responsibility - Abd. Kader, Ab. Saman (2004)
This paper highlights the scope of engineering education and their relevant to engineering profession being globally practiced in various sectors of development. The main objective of this discussion is to create awareness on the importance of engineering education in terms of their contents in responding to the work place requirement. It is to know about engineering profession by and large and also their scope of works in relation to engineer's roles and responsilities. The contents of engineering education and their dynamic development provide the tools for engineers to play their signifant roles and responsiblilities accross a multidiscipline of engineering profession. The behavioral of professional engineers through a standard code of ethics should create engineers ability to troubleshoot problems under various circumstances and propose a solution through a number of approaches to the benefit of community, nation as well as global integration.